EVALUATION OF DEEP EUTECTIC SOLVENT IONIC LIQUID AS ADDITIVE FOR FOAM STABILITY ENHANCEMENT IN OIL RECOVERY - MD ASRI, NUR ASYIMAH (2021)
Foam application in enhanced oil recovery (EOR) processes has been introduced to overcome some limitations which occur during gas flooding. In this process, foam stability in the presence of oil plays an important role which intensely determines the effectiveness of foam flooding. The addition of chemical additives has been proposed to enhance the performance of surfactant as a foaming agent. A new class of ionic liquid (IL), namely Deep Eutectic Solvent (DES) is considered to be able to alter surface behavior of surfactant molecules. Their alteration is expected to be favorable in improving surface properties of foam which increase the foam stability. The imidazolium- and eutectic-based ILs were used as additives to a fixed MFOMAX (M) surfactant concentration to assess the optimum amount of IL necessary for the best performance in the presence of oil.